Effect of β-tricalcium phosphate coated with zoledronic acid on human osteoblasts and human osteoclasts in vitro - Kadow-Romacker, Anke; Greiner, S.; Schmidmaier, Gerhard; Wildemann, B. (Journal of biomaterials applications, 2013)
The combination of a bone graft material with bisphosphonates (BPs) might be advantageous for an optimal balance of material resorption and stimulation of bone formation. This study investigated the effect of β-tricalcium phosphate (β-TCP) bone grafts coated with zoledronic acid (ZOL) on osteoblast-like cells and osteoclast-like cells (OLC). As a drug carrier, the polymer poly(D,L-lactide) was used and three different concentrations of ZOL were tested. β-TCP coated with ZOL stimulated the production of osteocalcin (OC), osteoprotegerin, and sRANKL in osteoblast-like cells. The polymer coating alone caused a significant increase in collagen type 1 and OC production. OLC viability was inhibited and the tartrate-resistant acidic phosphatase isoform-5b was significantly decreased after cultivation on polymer-coated β-TCP for 12 days. The three different concentrations of ZOL decreased cell viability and no TRAPiso-5b was detectable, indicating a strong reduction of the TRAPiso-5b after 12 days in culture. After 21 days in culture, only the higher ZOL concentrations significantly reduced cell viability and TRAPiso-5b. The results of this study show that coating of β-TCP with ZOL has stimulating effects on osteoblast-like cells. Additionally, an inhibition of osteoclasts was seen. The combination of this bone grafting material with BPs might, therefore, be effective in the treatment of large bone defects.
Gesehen am 13.04.2021
First published: August 23, 2011